(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article "Environment as an object of research in architectural design" is devoted to the analysis of the phenomenon of "architectural environment" in order to identify the qualities and capabilities of the design object that still is not taken into account in the design practice of DAE. The definitions of "environment" as an interdisciplinary phenomenon (philosophy, pedagogy, psychology, sociology, etc.) are considering, the concept of "architectural environment" is clarify in relation to the specifics of the designer’s professional activity. The characteristics, signs, properties, parameters, and criteria for the formation of the environment are established. Such positions as "boundaries and composition", "structural and component certainty" and the functions of the environment in the cultural context are also considered. This information is summarize in tables. A comparison of traditional and innovative methods and areas of research on the architectural environment. Emphasis is placed on the fundamental positions that remain outside the scope of researchers’ interests: environmental scenario, scene, dynamic composition, environmental situation and dialogues, spirit of the area, spirit of the times, atmosphere of the environment, lifestyle and artistic image of the architectural environment.